An Apology for the Scholarship of Teaching and Learning - Jacqueline M. Dewar (Park University, 2008)
This paper provides a defense of the scholarship of teaching and learning (SoTL). It first examines the roots of SoTL. It then offers examples of SoTL investigations that can be pursued in any discipline and places them within a taxonomy of SoTL questions. It suggest that SoTL might serve as a natural and organic response to the changing landscape and challenges of higher education in the 21st century. The paper closes with resources and suggested entry points into this work for interested faculty and institutions.